2010
DOI: 10.1523/jneurosci.3250-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Visual Responses of Superior Colliculus Neurons Depends on Stimulus Velocity

Abstract: Visually responding neurons in the superficial, retinorecipient layers of the cat superior colliculus receive input from two primarily parallel information processing channels, Y and W, which is reflected in their velocity response profiles. We quantified the timedependent variability of responses of these neurons to stimuli moving with different velocities by Fano factor (FF) calculated in discrete time windows. The FF for cells responding to low-velocity stimuli, thus receiving W inputs, increased with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…In fact, response magnitudes and Fano factor were negatively correlated (r = −0.65, P < 0.0001; Fig. 2A), consistent with earlier observations in the visual system (13,23,28,29).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, response magnitudes and Fano factor were negatively correlated (r = −0.65, P < 0.0001; Fig. 2A), consistent with earlier observations in the visual system (13,23,28,29).…”
Section: Resultssupporting
confidence: 91%
“…The main neurophysiological substrate for our information theory results is that the trial-to-trial spike-count variability in the neural responses, measured by the classical Fano factor, was smaller for stimuli that elicited responses with a larger average firing rate. This negative correlation between average firing rate and count variability generalizes earlier results obtained in the visual system (12,13,23,28,29) to the somatosensory system. From a mechanistic perspective, the negative correlation between average firing rate and count variability has been shown to depend on the neurons' refractory period (12,13).…”
Section: Variability In the Responses Of Single Vpm Neurons To Differentsupporting
confidence: 89%
“…We next studied the dynamics of the population in response to short acoustic clicks (duration, 5 ms; interclick interval, 2.5 or 3.5 s). We used a sliding spike count window (T = 50 ms) and computed the averaged instantaneous rate, spike count correlation ρ(t) (2,14,15), and spike count Fano factor (11)(12)(13) by performing the statistics across repeated stimulus presentations and averaged over single units or single-unit pairs (Methods). Similarly, we computed the instantaneous silence density S(t) using 20-ms bins.…”
Section: Resultsmentioning
confidence: 99%
“…In anesthetized rodents correlations decrease with brain state desynchronization (8,9) or when animals switch from quiet wakefulness to active whisking during waking (10). Moreover, the commonly observed drop of spiking variability following stimulus onset (11)(12)(13) seems to occur jointly with a transient decrease in correlation (2,14,15). These observations suggest that correlations reflect the dynamical state of the circuit more than its hardwired connectivity.…”
mentioning
confidence: 95%
“…Previous empirical studies reported that FFs change with stimulus due to negative correlations between FF and firing rate (6,39), whereas stimulus-dependent changes of trial-by-trial variability have only been observed in the midbrain and thalamus (40,41). Variations of noise correlations with respect to speed of moving targets and movement direction have been reported in pairs of MT and motor-cortical neurons, respectively (42,43).…”
Section: Discussionmentioning
confidence: 99%